IMPLEMENTASI KEGIATAN EKSPERIMEN PADA PEMBELAJARAN KONSEP RANGKAIAN LISTRIK UNTUK MENGURANGI MISKONSEPSI MAHASISWA - Theo Jhoni Hartanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The purpose of this article was to: (1) describe the initial understanding of students to the concept of direct current electrical circuits (series and parallel) before learning activities; (2) describe the understanding of the concept of direct current electrical circuits (series and parallel) after implementing experimental activities. The study using pre-experimental one-group pretest-posttest design with a sample of this study was the first year Physical Education Programâ€™ students of University of Palangka Raya for academic year 2015-2016, consisted 25 students. The conceptsâ€™ understanding of students before and after learning processes was analyzed by using the certainty of response index (CRI). Based on the result: (1) before the learning, the average percentage of students who misconceptions of 50.40%, 35.20 % did not understand the concept, and who understand the concept of only 14.40%; (2) After learning activities by applying the experiment, the average percentage of students who do not understand the concept of misconceptions and reduced respectively to 9.60% and 6.40%, while the students understand the concept of increasing to 84%. That is, learning activities by implementing this experiment can reduce misconceptions on Physical Education Programâ€™ students of University of Palangka Raya, in particular on the concept of direct current electrical circuits (series and parallel) . Keywords: misconceptions, experiments activities, electritical circuit